Studi Consumer Brand Engagement pada Media Sosial FnB (Food and Beverages) Brand di Indonesia untuk Meningkatkan Brand Loyalty dengan Teori Social Exchange - Sasono, Annisa Ajeng Putikasari; Masnita, Yolanda; Kurniawati, Kurniawati (Universitas Batanghari, 2024)
Consumer Brand Engagement (CBE) on social media is important in shaping consumers emotional and interactive engagement with brands, spanning cognitive, affective and behavioral dimensions. In Indonesia, brand loyalty in the food and beverage (FnB) industry is often challenging, with many brands struggling to retain consumers in a competitive and dynamic market. The purpose of this study is to examine the dynamics of Consumer Brand Engagement and its impact on brand love and brand loyalty. This research specifically aims to understand how brand interactivity, consumer involvement, and e-WOM can influence Consumer Brand Engagement and impact to increase brand loyalty. This study used a quantitative approach, which was conducted through an online survey involving 317 respondents, and SmartPLS software was used to conduct SEM-PLS data analysis. This study found that consumer involvement and e-WOM have a positive influence on Consumer Brand Engagement. Furthermore, Consumer Brand Engagement shows a positive influence on brand love and brand loyalty, indicating that active and meaningful interactions between consumers and brands through social media can increase brand loyalty. This research contributes and integrates the social exchange theory literature to provide a deeper understanding of consumer brand engagement, consumer involvement, e-WOM, brand love and brand loyalty. This research highlights the importance of applying consumer involvement and e-WOM in the context of FnB Brand's social media marketing activities in Indonesia. It offers valuable insights for marketers who want to increase Consumer Brand Engagement and brand loyalty.